Determinants of Electronic Health in Developing Countries - Mugo, David M.; Nzuki, David (My University, 2014)
Limitations of paper-based records are influencing a transition across the globe towards Electronic Health Records (EHRs) and in general electronic health (eHealth). However, despite the well documented benefits of eHealth, adoption particularly in developing countries remains a great challenge. Lessons learned from widespread implementation efforts can be used to encourage and inform the use of eHealth. This study evaluates the most current literature to establish the extent to which electronic health has been adopted in developing countries. The study has shown various determinants of electronic health adoption which will help countries particularly the developing ones come up with necessary interventions to accelerate the adoption. As part of future work, more studies need to be done, firstly to confirm the effect of the mentioned determinants in this paper in each developing country, secondly to find out other determinants of eHealth adoption and thirdly to show how developing countries’ cooperation on eHealth strategies can affect the journey towards eHealth adoption by these countries.
Keywords: electronic health; eHealth; ICT adoption; developing country